2014
DOI: 10.3109/09513590.2013.859242
|View full text |Cite
|
Sign up to set email alerts
|

Luteal phase support with progesterone in intrauterine insemination: a prospective randomized study

Abstract: In infertile patients treated with mildly ovarian stimulation with recombinant gonadotropins and IUI, luteal phase support with vaginal progesterone is not associated with higher livebirth rate or clinical pregnancy rate compared with patients who did not receive any luteal phase support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…However, no general agreement exists regarding the efficacy of this approach. In a recent prospective randomized trial 398 infertile patients were submitted to 893 cycles of ovulation induction with gonadotropins and IUI. After IUI, the patients in the supported group received vaginal micronized progesterone capsules 200 mg/day, and those in the control group did not receive any luteal phase support.…”
Section: The Role Of Progesterone As Luteal Phase Support After Ovulamentioning
confidence: 99%
“…However, no general agreement exists regarding the efficacy of this approach. In a recent prospective randomized trial 398 infertile patients were submitted to 893 cycles of ovulation induction with gonadotropins and IUI. After IUI, the patients in the supported group received vaginal micronized progesterone capsules 200 mg/day, and those in the control group did not receive any luteal phase support.…”
Section: The Role Of Progesterone As Luteal Phase Support After Ovulamentioning
confidence: 99%
“…On the contrary, our findings are not in favor of luteal phase support as clinical pregnancy rates were comparable between two groups. Nieto et al reported that in infertile patients treated with mildly ovarian stimulation with recombinant gonadotropins and IUI, luteal phase support with vaginal progesterone is not associated with a higher live birth rate or clinical pregnancy rate compared with patients who did not receive any luteal phase support [ 22 ]. Similar to these findings, a recent large multicenter randomised controlled study demonstrated that in patients treated with IUI after ovarian stimulation with gonadotropins, the clinical pregnancy rate was not statistically significantly higher after luteal phase support with a vaginal progesterone gel [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the luteal phase LH is in low level and it is possible these amounts are not necessary for stimulation of endometrium [5]. LH secretion in infertility treatment cycle may be was in low level 10 days after the treatment with GNRH agonist and unsatisfactory to luteal stage support [6].…”
Section: Discussionmentioning
confidence: 99%